Effects of traffic noise exposure on corticosterone, glutathione and tonic immobility in chicks of a precocial bird. Issue 1 (18th November 2019) - Flores, Romina; Penna, Mario; Wingfield, John C; Cuevas, Elfego; Vásquez, Rodrigo A; Quirici, Verónica
Abstract: Repeated exposure to traffic noise may be perceived as a succession of stressors, and therefore, noisy urban environments could lead to a state of chronic stress. In developing animals, glucocorticoids can have organizational effects on the hypothalamic–pituitary–adrenal axis in addition to the classic activation effects, so evaluating the effect of traffic noise during development is urgently needed. To our knowledge, to date six studies have investigated the effects of traffic noise on baseline corticosterone (CORT) and/or the stress response in birds during development; however, these studies were performed in nestling (altricial species), where confounding factors (e.g. communication between nestlings and parents) could mask the real impact of traffic noise on stress. In this study, we evaluated the effect of traffic noise (traffic noise group vs . rural noise group) on baseline levels of CORT and stress responses in chicks of a precocial bird species, the Japanese quail ( Coturnix japonica ). Because CORT can also decrease glutathione (GSH) levels (antioxidant and neurotransmitter/modulator), secondly by means of path analysis we investigated whether the strength of the association between CORT levels, GSH levels and tonic immobility (TI) varied in relation to treatment. We observed (i) similar baseline levels of CORT in both groups, (ii) a trend toward higher stress response in the traffic noise group ( P  = 0.08), (iii) similar TI duration in both groups, (iv) higher GSH levels in the traffic noise group and (v) differences in the strength and sign of the associations in relation to the treatment (traffic vs . rural). We conclude that the acoustic environment perceived during development has implications for physiology and behaviour; as more research is done on this topic, the need for sustainable urban planning will become clearer.